2023
DOI: 10.3390/healthcare11040607
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Consequences for Individuals Treated with Tocilizumab for Serious COVID-19 Infection

Abstract: There seem to currently be no therapeutic medications found for the severe coronavirus infection in 2019 (COVID-19). In light of this, it has been hypothesized that the immunomodulatory treatment known as tocilizumab can lessen the inflammatory response that occurs in the respiratory system, speed up the process of clinical benefit, lower the risk of death, and avert the need for ventilators. This randomized controlled trial (RCT) studied patients with a proven infection of SARS-CoV-2 and hyperinflammatory rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In the end, twenty-two studies were found to meet our inclusion criteria. 30–52 A complete representation of this study selection process is shown in Figure 1 .
Figure 1 PRISMA diagram of the study selection process of the randomized controlled trials (RCTs) included in the analysis for the treatment of COVID-19.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the end, twenty-two studies were found to meet our inclusion criteria. 30–52 A complete representation of this study selection process is shown in Figure 1 .
Figure 1 PRISMA diagram of the study selection process of the randomized controlled trials (RCTs) included in the analysis for the treatment of COVID-19.
…”
Section: Resultsmentioning
confidence: 99%
“… 31 , 33 , 34 , 36 , 38 , 44 , 46 , 47 Additionally, 3 (3/22, 14%) studies were funded by both private and non-private organizations, 49 , 51 , 52 and 6 studies (6/22, 27%) reported no funding. 30 , 37 , 39 , 40 , 43 , 48 The demographic and clinical characteristics of the included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations